Definitions, phenomenology, diagnosis, and management of the disorders of laughter and crying in amyotrophic lateral sclerosis (ALS): Consensus from ALS and Motor Neuron Disease Scientific Department of the Brazilian Academy of Neurology - Gondim, Francisco de Assis Aquino; Pinto, Wladimir Bocca Vieira de Rezende; Chieia, Marco Antônio Troccoli; Correia, Carolina da Cunha; Cunha, Francisco Marcos Bezerra; Dourado Jr, Mário Emílio Teixeira; França Júnior, Marcondes Cavalcante; Marques Júnior, Wilson; Oliveira, Acary Souza Bulle; Rodrigues, Cleonisio Leite; Silva, Delson José da; Dias-Tosta, Elza (Arquivos de Neuro-Psiquiatria, 2023)
The spectrum of neuropsychiatric phenomena observed in amyotrophic lateral sclerosis (ALS) is wide and not fully understood. Disorders of laughter and crying stand among the most common manifestations. The aim of this study is to report the results of an educational consensus organized by the Brazilian Academy of Neurology to evaluate the definitions, phenomenology, diagnosis, and management of the disorders of laughter and crying in ALS patients. Twelve members of the Brazilian Academy of Neurology - considered to be experts in the field - were recruited to answer 12 questions about the subject. After exchanging revisions, a first draft was prepared. A face-to-face meeting was held in Fortaleza, Brazil on 9.23.22 to discuss it. The revised version was subsequently emailed to all members of the ALS Scientific Department from the Brazilian Academy of Neurology and the final revised version submitted for publication. The prevalence of pseudobulbar affect/pathological laughter and crying (PBA/PLC) in ALS patients from 15 combined studies and 3906 patients was 27.4% (N = 1070), ranging from 11.4% to 71%. Bulbar onset is a risk factor but there are limited studies evaluating the differences in prevalence among the different motor neuron diseases subtypes, including patients with and without frontotemporal dementia. Antidepressants and a combination of dextromethorphan and quinidine (not available in Brazil) are possible therapeutic options. This group of panelists acknowledge the multiple gaps in the current literature and reinforces the need for further studies.
Keywords: Amyotrophic Lateral Sclerosis; Emotional Incontinence; Pathological Laughter and Crying; Pseudobulbar Affect; Affective Symptoms; Emotional Regulation; Affect